Titanium Alkoxide Complexes as Catalysts for the Synthesis of Cyclic Carbonates from Carbon Dioxide and Epoxides. Issue 32 (21st October 2015) - Al‐Qaisi, Feda'a; Streng, Emilia; Tsarev, Alexey; Nieger, Martin; Repo, Timo
Abstract: Titanium alkoxides can catalyze efficient and selective synthesis of cyclic carbonates through CO2 insertion into epoxides when tetrabutylammonium bromide or iodide is used as a cocatalyst. Of the series of synthesized titanium alkoxides, the most active catalyst was one bearing an aliphatic bidentate alkoxide ligand, and it produced propylene carbonate under benign conditions (100 °C, 15 bar CO2, 3 h) with turnover frequencies of up to 116 h –1 . The effect of reaction parameters such as pressure, temperature, and catalyst/cocatalyst molar ratio were also studied in order to optimize the catalytic system. Abstract : New titanium alkoxide complexes were synthesized and characterized, and their catalytic activity with ammonium salts or amines as cocatalysts for selective synthesis of cyclic carbonates from epoxides and carbon dioxide was investigated.